Petrographic and geochemical features of Mouriscas Orthogneisses: contribution to Ossa-Morena Zone geodynamical model - Henriques, S.B.A. (2020)
ABSTRACT: A preliminary study presents a set of variscan granitoids, which intruded the Ossa Morena Zone (OMZ), at the Arraiolos-Pavia region. Field, petrographic and geochemical characterization defines the bases for a general classification of the Ossa Morena Zone granitoids, similar to that of Central Iberian Zone (CIZ). The obtained data pointed out the occurrence of enormous volumes of basic and intermediated compositions. Granitoids containing biotite, amphibole and calcic plagioclase, granitoids are frequent, showing particular features of the OMZ, relatively to the CIZ. Geochemical data indicate sub-alkaline sequences and different magmatic sources, from mantle and crust. These sequences have reached different stages of magmatic evolution. The most evolved melts are enriched in alkalis gave compositions for the alkaline field in the TAS diagram (alkali feldspar granite). These evolved rocks have the Al2O3 values of granites.